Implementasi Akad Murabahah pada Produk Pembiayaan KPR di Bank Syariah Indonesia KC Cimahi - Asri Mariam Syarah; Lasmi Wardiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the implementation of the murabahah contract in the Home Ownership Credit (KPR) financing product at Bank Syariah Indonesia (BSI) Cimahi Branch Office. This study uses a descriptive qualitative method with data collection through interviews, observation, and documentation. The results show that the KPR financing mechanism at BSI Cimahi Branch Office has been running in accordance with sharia principles established by the National Sharia Council (DSN-MUI). The process starts from customer application, wakalah contract, to the implementation of the murabahah contract with the principle of transparency of the principal price and profit margin agreed in advance and fixed throughout the financing tenor. The implementation of this system provides payment certainty for customers and protects against the risk of interest rate fluctuations. In terms of performance, Murabahah KPR financing at BSI Cimahi Branch Office has contributed significantly to the financing portfolio with a low level of Non-Performing Financing (NPF) and positive growth every year. However, challenges still exist in the amount of the down payment and the attachment of a fixed margin that can be a burden for customers with limited financial capabilities. Overall, the murabahah contract has proven to be an effective, transparent, and sharia-compliant instrument in supporting home ownership for the Muslim community in Indonesia.